Interactive Reports in SAS Visual Analytics : Advanced Features and Customization. - Ball, Nicole (SAS Institute, 2021)
Elevate your reports with more user control and interactive elements Want to create exciting, user-friendly visualizations to bring greater intelligence to your organization? By mastering the full power of SAS Visual Analytics, you can add features that will enhance your reports and bring more depth and insight to your data. Interactive Reports in SAS Visual Analytics: Advanced Features and Customization is for experienced users who want to harness the advanced functionality of Visual Analytics on SAS Viya to create visualizations or augment existing reports. The book is full of real-world exa.